2018
DOI: 10.1128/jcm.01457-17
|View full text |Cite
|
Sign up to set email alerts
|

A Gastrointestinal PCR Panel Improves Clinical Management and Lowers Health Care Costs

Abstract: Conventional methods for the identification of gastrointestinal pathogens are time-consuming and expensive and have limited sensitivity. The aim of this study was to determine the clinical impact of a comprehensive molecular test, the BioFire FilmArray gastrointestinal (GI) panel, which tests for many of the most common agents of infectious diarrhea in approximately 1 h. Patients with stool cultures submitted were tested on the GI panel ( = 241) and were compared with control patients ( = 594) from the year pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 12 publications
2
89
1
Order By: Relevance
“…In line with previously conducted studies, the diagnostic yield was higher using the FilmArray GI panel: one or more pathogen was detected in 39.6% of the patients compared to 28.6% by routine PCR. [8,19,20] Furthermore, The Fil-mArray detected pathogens that were included in the routine PCR panels, but were not ordered by the clinician and it detected pathogens that were not on any of the routine PCR panels. Using the FilmArray, time to result was significantly shortened compared to routine PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previously conducted studies, the diagnostic yield was higher using the FilmArray GI panel: one or more pathogen was detected in 39.6% of the patients compared to 28.6% by routine PCR. [8,19,20] Furthermore, The Fil-mArray detected pathogens that were included in the routine PCR panels, but were not ordered by the clinician and it detected pathogens that were not on any of the routine PCR panels. Using the FilmArray, time to result was significantly shortened compared to routine PCR.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Furthermore, depending on the laboratory routine, turn-around times of one or more days is common practice, during which a patient is isolated with empirical therapy or no therapy at all. [8] The BioFire FilmArray GI Panel (BioFire Diagnostics) contains 22 of the most common GI pathogens in a single panel. With this random access test, the hands-on time is reduced to around 3 minutes and the test has a turnaround time (TAT) of about one hour.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the FilmArray GI panel has implications regarding other aspects of patient care, including use of hospital resources and infection control. Beal et al found a modest reduction in LOS, days of antibiotics, abdominal imaging studies, and costs per patient associated with the use of the FilmArray GI panel; however, in that study the FilmArray GI panel results were not communicated to physicians in a timely manner, likely reducing their impact on management [29]. In a cost-benefit analysis, the use of the Luminex xTAG gastrointestinal panel was associated with increased diagnostic costs but break-even points and cost savings could be realized contingent on using the test results to reduce isolation days [30].…”
Section: Discussionmentioning
confidence: 89%
“…The use of the FilmArray GI panel has implications regarding other aspects of patient care, including use of hospital resources and infection control. Beal et al found a modest reduction in LOS, days of antibiotics, abdominal imaging studies, and costs per patient associated with the use of the FilmArray GI panel; however, in that study the FilmArray GI panel results were not communicated to physicians in a timely manner, likely reducing their impact on management [29]. In a cost-bene t analysis, the use of the Luminex xTAG gastrointestinal panel was associated with increased diagnostic costs but break-even points and cost savings could be realized contingent on using the test results to reduce isolation days [30].…”
Section: Discussionmentioning
confidence: 89%